Low-temperature dynamics of (S)-4-(1-methylheptyloxy)-4ʹ-cyanobiphenyl (8*OCB) and (S)-4-(2-methylbutyl)-4ʹ-cyanobiphenyl (5*CB) in disordered crystalline and glassy phases. Issue 1 (2nd January 2019) - Krawczyk, J.; Massalska-Arodź, M.; Rozwadowski, T.
ABSTRACT: The inelastic neutron scattering (INS) spectra were measured for two materials of chiral molecules: (S)-4-(1-methylheptyloxy)-4ʹ-cyanobiphenyl (8*OCB) and (S)-4-(2-methylbutyl)-4ʹ-cyanobiphenyl (5*CB), revealing solid state polymorphism with two partially disordered crystalline phases I and II and glassy state of liquid and of crystalline phase in each substance. The experiments were performed in the energy range up to 30 µeV in the temperature range from 4 to 35 K. For 8*OCB the elastic scans were measured as well up to 300 K illustrating well the phase diagram. For all solid phases of both substances in the µeV range of INS spectra, the existence of the excess density of vibrational states over that typical for fully ordered crystalline phases was evidenced. Contribution of this so-called boson peak occurred to be much larger in glass of isotropic phase than in the phase II and glass of phase I of 8*OCB, while for 5*CB it was larger in the phase I and glass of phase II than in glass of cholesteric phase. The quasi-elastic broadening of elastic peak corresponding to stochastic reorientations in the ns time scale was detected for both substances. Comparison of the results obtained for glassy and crystalline phases of 8*OCB and 5*CB compounds have been given and confronted with those obtained previously in meV energy range. GRAPHICAL ABSTRACT: